The Cassette in 1980s Indie Music Scenes. Issue 2 (4th May 2019) - Drew, Rob
ABSTRACT: The cassette format took on three central functions within 1980s independent music (indie) in the United States: It served as a means of connection among musicians, facilitated the process of auditioning, and allowed formal distribution through cassette-only releases. In all these capacities, the cassette served simultaneously as an instrument of diffusion and as a token of intimacy and community, values essential to indie's self-image. In turn, indie highlighted the commercial potential and interpersonal resonance of the cassette format, helping to save the cassette from its reputation as a facilitator of piracy. At the same time, the cassette forced indie scenes to acknowledge the limits of their communitarian ethos.